Impact of ergonomic interventions on musculoskeletal health among Thai para rubber workers: evaluating workstation improvements - Ratchanee Joomjee; Nopparat Songserm; Wilawun Chada; Turnbull, Niruwan (International Journal of Occupational Safety and Health, 2025)
Introduction: Musculoskeletal disorders (MSDs) are a significant occupational health issue among rubber plantation workers in Thailand. This study evaluates the effectiveness of ergonomic interventions in reducing MSD risks in Ubon Ratchathani Province. Methods: A quasi-experimental design was used to study 96 workers across urban (UA), semi-urban (SA), and rural (RA) areas. Participants were divided into three groups: a control group (RA), a training-only group (SA), and a group receiving both ergonomic training and workstation improvements (UA). Data were collected using the Nordic Musculoskeletal Questionnaire and Rapid Entire Body Assessment (REBA) tool before and after the interventions. Paired sample t-tests were conducted to analyze changes in REBA scores and ergonomic knowledge. Results: The UA group, which received workstation improvements, showed a significant reduction in REBA scores from 13.22 (very high risk) to 6.47 (medium hazard) (p < 0.001). The SA group exhibited improved training scores (p < 0.005) but no significant reduction in ergonomic risks. The RA group showed no significant changes. Conclusion: The study demonstrates that while ergonomic training improves knowledge, it does not effectively reduce ergonomic risks without corresponding physical modifications to the work environment. Workstation improvements significantly lowered MSD risks in the UA group. These findings suggest that a combined approach of training and environmental interventions is necessary to improve occupational health outcomes in high-risk settings like rubber plantations.